Pervasiveness of child sexual abuse in Kisii county during the Covid-19 pandemic (African Journal of Science, Technology and Social Sciences, 2022)
Child sexual abuse (CSA) is both a social and public health concern locally and globally. A mutual mistaken belief on child sexual abuse is that, it is uncommon occurrence committed against girls by male strangers in both rural and urban areas in Kenya. Notwithstanding myriad research on CSA, little is known about its Pervasiveness. It occurs at all levels of the society affecting not only girls but also boys. The purpose of this study therefore was to investigate the pervasiveness rate of child sexual abuse among pupils during the COVID-19 pandemic. The COVID-19 plague is a international historic incident that will remain to affect approximately every facet of ordinary life, including affecting our economic, political, and healthcare eco-systems. The study was informed by the Attachment Theory which suggests that children’s lives are centered initially on their parents, the family environment being their primary agent of socialization. Systematic random sampling was used to select the respondents to ensure that the sample was a representative. The study utilized descriptive survey design. The study population was 700 pupils out of which a sample size of 100 (14 percent) pupils was selected. The study used questionnaires administered to each respondent. The researcher administered the questionnaires individually to all respondents. The study found out that threats from perpetrators were preventing the disclosure of child sexual abuse. The research recommends that research, programs and policies should focus on child protection. The patriarchal narrative of manhood needs to change and boys should read from a different script on their roles and place in the society.
Keywords: Attachment theory; Patriarchal narrative; Socialization; perpetrators; COVID-19